Pengaruh Perilaku Menabung terhadap Perilaku Finansial dan Kepuasan Finansial pada Anggota Koperasi Simpan Pinjam: Apakah Gender menjadi Moderator? - Lucia Iswandari (Value : Jurnal Manajemen dan Akuntansi, 2025)
In the midst of the current economic dynamics of society, especially for members of savings and loan cooperatives, individual behavior in managing finances is very important. This study aims to examine the effect of saving behavior on financial behavior that mediates financial satisfaction by considering the moderating role of gender. This study was conducted by taking samples using purposive sampling on active members of savings and loan cooperatives in the Special Region of Yogyakarta. The analysis method of this research used a regression approach by applying PROCESS Macros Ver. 5.0 for SPSS. The results of the study indicated that saving behavior has a positive and significant effect on financial behavior, and financial behavior has a significant effect on financial satisfaction. However, the direct and indirect effects of saving behavior on financial satisfaction was not significant. In addition, a gender moderation effect was found, where the relationship between savings behavior and financial behavior was stronger in female than in male respondents. The results of this study encourage the development of financial education that not only emphasizes savings, but also the formation of healthy financial behavior, by considering differences in gender characteristics.